2014
DOI: 10.1002/bdra.23241
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in bronchopulmonary dysplasia

Abstract: Pulmonary hypertension is common in bronchopulmonary dysplasia and is associated with increased mortality and morbidity. This pulmonary hypertension is due to abnormal microvascular development and pulmonary vascular remodeling resulting in reduced cross-sectional area of pulmonary vasculature. The epidemiology, etiology, clinical features, diagnosis, suggested management, and outcomes of pulmonary hypertension in the setting of bronchopulmonary dysplasia are reviewed. In summary, pulmonary hypertension is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 44 publications
0
40
0
1
Order By: Relevance
“…Recently, a retrospective cohort study identified peak BNP levels as a prognostic marker for all-cause mortality in extremely-low-BW infants with BPD-associated PH [11]. It has been suggested that serial BNP may be useful for following the course of PH in this population [1]. However, this is the first prospective study to propose BNP levels >1,000 pg/ml as a screening tool for PH in infants with BPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a retrospective cohort study identified peak BNP levels as a prognostic marker for all-cause mortality in extremely-low-BW infants with BPD-associated PH [11]. It has been suggested that serial BNP may be useful for following the course of PH in this population [1]. However, this is the first prospective study to propose BNP levels >1,000 pg/ml as a screening tool for PH in infants with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hypertension (PH) occurs in approximately 14-37% of prematurely born infants with bronchopulmonary dysplasia (BPD) [1]. It is associated with a significant mortality risk, as high as 38%.…”
Section: Introductionmentioning
confidence: 99%
“…Wistar rats 2,3 were selected at random on days 3, 7 and 14 after the experiment had commenced. pentobarbital sodium (3%) was injected intraperitoneally (1 mL/100 g body weight) to sacrifice the rats.…”
Section: Isolation Culture and Identification Of Lfs In Vitromentioning
confidence: 99%
“…En nuestro centro empleamos habitualmente inicio de tratamiento con sildenafil como primera lí-nea cuando los pacientes presentan HP secundaria a DBP severa, luego de haber evaluado y tratado pertinentemente otras posibles etiologías subyacentes. En caso de no responder, se podría agregar bosentán o iloprost según la experiencia del equipo tratante y las características del paciente específico 8,21 .…”
Section: Terapias Específicasunclassified